Diagnosis Penyakit Sapi Menggunakan Metode Promethee - Bayu Kusuma Pradana; Nurul Hidayat; Randy Cahya Wihandika (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Indonesia has the potential of a large farm with superior products such as dairy cattle and beef cattle, the superior products of these farms are growing and concentrated in the development area of ​​the production center. With large amounts of production, the need for animal protein in Indonesia is increasing with increasing public awareness of the importance of nutritional intake. Therefore, the health of livestock raised by farmers is important to meet the nutritional needs and in addition to income for the livestock owners themselves. Promethee is a method of determining the order (priority) in multicriteria analysis. The key issues are simplicity, clarity, and stability. Promethee method is well used for the diagnosis of disease in cattle because it produces an accuracy of 92.73%.